The Pursuit of Pleasure on TikTok Between Eros and Consumption as a Matter of Popular Habitus - Graziano, Roberto (Italian Sociological Review, 2026)
Amid ongoing debates on the platformisation of consumer culture, in which both the value of commodities and the processes through which subjective identities are shaped are increasingly mediated by digital infrastructures, TikTok appears to reconfigure the relationship between platforms and local contexts. Rather than simply amplifying globalised aesthetic models, the platform enables forms of bottom-up visibility through which popular cultures articulate and display their own modes of self-representation, deeply embedded in specific autochthonous settings. In this exploratory study, I examine how young people from the Neapolitan popular milieu construct models of desirable masculinity, and how local creators simultaneously contribute to the emergence of a popular gastronomic aesthetic, defined here as gourmand. Through the qualitative analysis of digital content, the two case studies provide an analytical lens to investigate how subjects who embody a popular habitus participate in the mediated reproduction of Neapolitan popular culture on TikTok.